Linking service convenience to satisfaction: dimensions and key moderators. Issue 6 (11th September 2017) - Benoit, Sabine; Klose, Sonja; Ettinger, Andreas
Abstract : Purpose: Demand for service convenience, defined as a consumer's perception of minimized time and effort spent to obtain a service, has increased in conjunction with certain sociocultural and demographic changes. Previous research notes the significance of service convenience, but the importance of different dimensions of service convenience and the role of key moderators affecting the link between convenience and satisfaction (like customer psychographic and sociodemographic characteristics) remain unaddressed. Thus, the purpose of this research is to identify those customer groups for which offering convenience will have the highest leverage to increase satisfaction. Design/methodology/approach: Two models are developed and tested: a multidimensional model of service convenience with a formative measure of five service convenience dimensions, namely, decision, access, search, transaction and after-sales convenience, and a moderator model hypothesizing different customer psychographic and sociodemographic characteristics (time pressure, shopping enjoyment, age, household size and income) that affect the link between service convenience and satisfaction. Findings: This study reveals that search convenience, followed by transaction and decision convenience, exerts the greatest influence on the perception of overall service convenience. In addition, those who value service convenience most are high-income, time-pressed consumers in smaller households who experience low shopping enjoyment. Originality/value: Providers have limited budgets for enhancing their services. Thus, it is important to identify which dimension has the greatest influence on the perception of service convenience and the customer segments for which service convenience is most critical.